LITERASI DIGITAL SISWA SEKOLAH DASAR: PENGGUNAAN BAHAN AJAR BERBASIS DIGITAL PADA PEMBELAJARAN BAHASA INDONESIA - Muhammad Hafidhi, Nur; Hanafi, Yusuf; Hadi, Syamsul; Suyitno, Imam; Eka Anggraini, Ade (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The ease and breadth of information that the community can access makes technology like a double-edged sword that can hurt its users, therefore being wise and responsible in utilizing technology is important for every individual in the digital era, especially for elementary school students. The study aims to explore using digital-based teaching materials to instill digital literacy in elementary school students learning Indonesian. The research method used was a phenomenological qualitative approach, involving teachers and four grade III students as research subjects. Data collection was conducted through observation, interviews, and document analysis, with data analysis using an interactive cycle. The results showed that the use of the Madurese folklore flipbook had a significant positive impact by creating fun learning for students, students gained new learning experiences, and students who did not have mobile phones could find out how to use mobile phones, especially to access learning materials. Nevertheless, there are some obstacles in the implementation of digital-based learning, such as Wi-Fi network interference and students' lack of focus in following the selected story. Teachers can maximize the use of digital-based teaching materials by giving intensive attention to students who are less focused and providing additional understanding related to the selected story. This research contributes to the understanding of students' digital literacy and expands knowledge about the development of teaching materials to improve digital literacy at the primary school level.